Prioritizing Franchise Expansion with AHP: Strategic Evaluation of Special Product Placement in Minimarkets - Miranda, Ivanca Earltina; Hidayatno, Akhmad (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study examines the strategic decision-making process involved in expanding franchise minimarkets by pinpointing optimal locations for launching special product offerings. Utilizing the Analytical Hierarchy Process (AHP), the research assesses eight alternative location types to establish priority rankings based on various decision criteria. Data were gathered through structured questionnaires administered to expert respondents, and pairwise comparisons were performed to evaluate the relative importance of both criteria and alternatives. The analysis identifies rest areas on toll roads as the most advantageous locations for expansion, followed by vertical residential complexes and office buildings. Among the criteria, potential customer volume and daily traffic flow proved to be the most influential factors in the decision-making process. Consistency ratio analysis verified the reliability of the AHP model. These findings offer actionable insights for franchise operators, highlighting the importance of targeting high-traffic locations to improve sales performance and operational efficiency. The study concludes that prioritizing rest area locations can significantly facilitate strategic growth and the effective placement of special products within existing minimarkets.